POTENSI EKSTRAK BUNGA KLUWIH (Artocarpus altilis Linn) SEBAGAI INSEKTISIDA terhadap KEMATIAN NYAMUK Aedes aegypti Linn dengan METODE ELEKTRIK CAIR - Faizatun Nikmah; Sulistyani Sulistyani; Retno Hestiningsih (Jurnal Kesehatan Masyarakat (Undip), 2016)
Dengue hemorrhagic fever is a disease that was dangerous to people live  was transmitted through mosquito bites Ae.aegypti Linn. In Indonesia, the amount of dengue cases tended to increase from year to year. One of efforts to control dengue was the used of anti-mosquito. One of the useful plants as a natural insecticide was breadfruit flower (Artocarpus atilis Linn). Breadfruit flower contains flavonoids, saponins, polyphenols were useful as a vegetable insecticide. This study aimed to determine the potential of breadfruit extract (Artocarpus altilis Linn) as an insecticide against mosquitoes death Ae.aegypti Linn. This research used a true experiment with design Randomized Control Trial. Method for making flower extract artocarpus altilis was maceration. The number of samples tested as much as 720 mosquitoes Ae.aegypti Linn aged 2-5 days with each of the 20 mosquito on any treatment unit. The trial method used liquid electric with glass chamber. the researcher did the reseach in 3 times replication with concentration of Artocarpus altilis Linn extract 17%, 24%, 32%, 73%, and 96%. those concentration already used LC50 standard of Arto extract. based on probit analysis, this research showed that LC50 of Artocarpus altilis Linn extract is 73%. The one way ANOVA reseacrh analysis showed that the significant grade 0,001 (p<0,05), H0 rejected, which shown that there is dissimilarity death average from the different serial concentration. The usage of Artocarpus altilis Linn extract is for an alternative nature insecticide in controlling Ae.aegypti Linn vector because the researcher proved that using the liquid electric has potential as insecticide toward Ae.aegypti Linn. Expected to further research using other methods techniques to elevate again the level of concentration.